# Conditional convergence of $\sum \frac{(-1)^{[\sqrt{n}]}}{n^{p}}$

I need to prove that the following series:

$$\sum \frac{(-1)^{[\sqrt{n}]}}{n^{p}}$$

is conditionally convergent when p=1.

Any hints would be welcome.

-
The exponent, is it floor of $\sqrt n$ or round of $\sqrt n$? – Ricbit Nov 18 '12 at 14:38
Welcome to math.SE: since you are new, I wanted to let you know a few things about the site. In order to get the best possible answers, it is helpful if you say in what context you encountered the problem, and what your thoughts on it are; this will prevent people from telling you things you already know, and help them give their answers at the right level. – Julian Kuelshammer Nov 18 '12 at 14:38

Consider that: $$\sum_{n=1}^{(m+1)^2-1}\frac{(-1)^{\lfloor\sqrt{n}\rfloor}}{n}=\sum_{k=1}^{m}\sum_{n=k^2}^{(k+1)^2-1}\frac{(-1)^k}{n},$$ and: $$\frac{2k+1}{k^2+2k}\leq a_k=\left|\sum_{n=k^2}^{(k+1)^2-1}\frac{(-1)^k}{n}\right|\leq\frac{2k+1}{k^2}.$$ We have: $$\sum_{n=1}^{(m+1)^2-1}\frac{(-1)^{\lfloor\sqrt{n}\rfloor}}{n}=\sum_{k=1}^{m}(-1)^k\, a_k,$$ and since $\left|a_k-\frac{2}{k}\right|\leq\frac{C}{k^2}$, the RHS of the last expression is a conditionally convergent series. Moreover, $$\left|\sum_{n=1}^{M}\frac{(-1)^{\lfloor\sqrt{n}\rfloor}}{n}-\sum_{n=1}^{\lfloor\sqrt{M+1}\rfloor^2-1}\frac{(-1)^{\lfloor\sqrt{n}\rfloor}}{n}\right|\leq\frac{2\sqrt{M+1}}{M},$$ and since the RHS of the last expression converge to zero when $M$ approaches $+\infty$, the original series is conditionally convergent, too.
Here I assumed that the exponent of the $(-1)$ in the original series was the floor function of $\sqrt{n}$, but, with minor adjustments, the same argument works for the round function, too.